The impact of reintroduced Eurasian beaver (Castor fiber) dams on the upstream movement of brown trout (Salmo trutta) in upland areas of Great Britain - Robert J. Needham; Richard W. Zabel; Dylan Roberts; Paul S. Kemp (PLoS ONE, 2025)
The return of Eurasian beaver (Castor fiber) to large areas of Europe represents a conservation success with the current population estimated to be around 1.2 million individuals. Their reintroduction to many areas, including Great Britain, has in some cases been controversial. Despite numerous documented benefits to biodiversity, concerns relate to localised flooding, adverse impacts on land use and engineered structures (e.g. culvert blockage), disease transfer, and the influence of beaver habitat modifications on fisheries, particularly in relation to salmonids. This study investigated the impacts of a series of four beaver dams on the upstream movement of brown trout during the spawning period (October—December) at a field site in Scotland. The study site comprised two streams entering a common loch, one modified by a series of four beaver dams, the other remaining unaltered during the Study Period. Trout were captured using electric fishing, fyke nets and rod and line and were tagged with Passive Integrated Transponders (PIT) before release. PIT telemetry antennas were installed below and above each dam to establish successful passage of trout during the monitoring period that included trout spawning movements in 2015 (high flows) and 2016 (low flow). There was a distinct difference in passage success between years, with high flows (using prior rainfall as a proxy measure) and larger fish size being important positive predictors of upstream passage success. A combination of environmental (prior rainfall and water temperature) and biotic (fish size) factors influenced passage success with high flows being a significant covariate at all four dams in two models used to define trout passage dynamics (Weibull and exponential base models), providing the best explanatory variable for fish passage at two of the four dams. Survival analysis and associated modelling indicated that migratory delay was inversely related to previous passage success, whilst motivation was also a determinant of success, with greatest passage in highly motivated trout. Our findings indicate that given the right environmental and biotic factors, brown trout are adept at passing beaver dams, although under certain conditions, beaver dams can impede the movement of brown trout and the magnitude of impact is influenced by these factors. In particular, the barrier effects of beaver dams are exacerbated under low flow conditions, and this may become a greater challenge in the future due to shifting climatic conditions if periods of warmer and drier weather persist and coincide with peak migratory movements of fish.